The Development of Farmer Agrarian Literacy in Facing Changes in Times (Sample Framework in Ngawi Regency) - Riyanto, Sugeng; Wahyuni, Lilik; Muchlisyiyah, Jhauharotul; Prasetyaningrum, Dian Islami (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2021)
Increased infrastructure development has significantly impacted world agriculture, generally in Indonesia and particularly in Ngawi Regency. Due to the narrowing of agricultural land is an unavoidable necessity. It can be seen in the annual loss of agricultural land due to the eroded flow of development, which will doubt harm agricultural production. Because the agricultural land is decreasing, achieving food self-sufficiency in the world in the coming years will be difficult. The fact is the cause of the narrowness of agricultural land for infrastructure development. In addressing the issues mentioned above, research into the knowledge/literacy of farmers in the Ngawi Regency is required; specifically, developing farmer knowledge will enable farmers to continue farming. According to the research's findings: farmers have a deep understanding of agriculture; they mostly learn from their parents, the Internet, and neighbors; farmers learn about pest and disease cultivation and marketing aspects from the Internet.